69.1k views
3 votes
Find the inverse of g(x) = 2x^3 +3

Step by step working please I want to learn

User MattDavis
by
6.0k points

2 Answers

3 votes

Set g(x) as y. Then you get y = 2x^3 + 3. Switch Y with X and you get x = 2y^3 + 3. Now you can put everything with x getting, y = cuberoot[(x-3)/2]

User Marissa
by
4.7k points
4 votes


g(x)=2x^3+3\to y=2x^3+3

replace x with y


2y^3+3=x\ \ \ |-3\\\\2y^3=x-3\ \ \ |:2\\\\y^3=(x-3)/(2)\to y=\sqrt[3]{(x-3)/(2)}

Answer:
g^(-1)(x)=\sqrt[3]{(x-3)/(2)}

User Hiltmon
by
6.0k points